Study of Υ(10753) decays to π + π − Υ(nS) final states at Belle II - The Belle II collaboration; I. Adachi; L. Aggarwal; H. Ahmed; H. Aihara; N. Akopov; A. Aloisio; N. Anh Ky; D. M. Asner; H. Atmacan; T. Aushev; V. Aushev; et al. (Journal of High Energy Physics)
Abstract We present an analysis of the process e + e − → π + π − Υ(nS) (where n = 1, 2, or 3) reconstructed in 19.6 fb −1 of Belle II data during a special run of the SuperKEKB collider at four energy points near the peak of the Υ(10753) resonance. By analyzing the mass distribution of the π + π − Υ(nS) system and the Born cross sections of the e + e − → π + π − Υ(nS) process, we report the first observation of Υ(10753) decays to the π + π − Υ(1S) and π + π − Υ(2S) final states, and find no evidence for decays to π + π − Υ(3S). Possible intermediate states in the π + π − Υ(1S, 2S) transitions are also investigated, and no evidence for decays proceeding via the π ∓ Z b ± $$ π^{\mp }{Z}_b^{± } $$ or f 0(980)Υ(nS) intermediate states is found. We measure Born cross sections for the e + e − → π + π − Υ(nS) process that, combined with results from Belle, obtain the mass and width of Υ(10753) to be (10756.6 ± 2.7 ± 0.9) MeV/c 2 and (29.0 ± 8.8 ± 1.2) MeV, respectively. The relative ratios of the Born cross sections at the Υ(10753) resonance peak are also reported for the first time.